(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Exposed to the natural sources are risk, as a result of human activity aimed to get the food and agricultural raw materials. This leads to the weakening of the capacity of the resources to fulfill the needs of future generations. Therefore, it is important to preserve the environment and natural resources of interest to scientists. This resulted in the birth of the sustainable agricultural development. The importance of this research is derived from the importance of agriculture to sustain life, it is impossible to do without food. Therefore, it should work to reduce the negative impacts of agriculture on the environment, and at the same time working to improve the positive effects too. The research aims at identifying the levels which were completed towards sustainable agricultural development at the global level in the group of developed and developing countries . The research found that agriculture was able to increase the per capita calorie intake, in conjunction with the increasing use of external inputs harmful to the environment. But the developed countries started to go towards reducing these inputs, while developing countries still tend to increase their use.